ANALISIS KREATIVITAS BISNIS TERHADAP KEUNGGULAN BERSAING PADA PERCETAKAN UNDANGAN PERNIKAHAN DI KOTA TIMIKA - Muh Sabir; Rima Diman (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2022)
This study aims to determine the analysis of business creativity on competitive advantage in a wedding invitation printing in Timika City. The research method used is a descriptive method, which is a research method that describes or describes something, for example conditions, conditions, situations, activities, and others. In this study the data collection techniques used were observation, interviews, and questionnaires. To find out business creativity of competitive advantage in a wedding invitation printing in the city of Timika, the analysis used in this study is the analysis of the chi square of the sample. The results showed that there was an influence on business creativity on competitive advantage on a wedding invitation printing in the city of Timika, which means the authenticity of the product, the transformation of a product and the feasibility of the product from the indicator of business creativity on competitive advantage has an influential results in the city of Timika.